Automated Diagnostics in Medicine and Their Role in Reducing Human Error (Texas Journal of Medical Science, 2025)
Automated diagnostic systems have become integral to modern medicine, offering significant improvements in the accuracy and efficiency of disease detection. By utilizing artificial intelligence, machine learning, and advanced data analysis techniques, these systems reduce the dependency on human judgment, which can be prone to errors caused by fatigue, bias, or varying levels of expertise. This paper explores the role of automated diagnostics in minimizing human error, enhancing diagnostic consistency, and supporting clinicians in making informed decisions. The benefits of automated tools, such as improved detection of subtle medical conditions and standardized evaluation protocols, are discussed alongside challenges related to integration, ethical considerations, and the necessity of maintaining human oversight. The study highlights the potential of automated diagnostics to improve patient safety and healthcare quality while emphasizing their complementary role in clinical practice.